2009
DOI: 10.1007/s11332-009-0072-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of eye movement in upright postural control

Abstract: Vision contributes to upright postural control by providing afferent feedback to the cerebellum. Vision is generally classified into central and peripheral vision. In measurements of postural sway, in which participants are required to maintain a stable upright posture while fixating on a visual target, non-retinal eye positional information due to the fixation is used as well as the retinal information from both visual fields. However, little is known about the role of non-visual eye positional information in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The observation that balance control during the PAD condition was not related to executive function measures is intriguing given that standing on an unstable base of support decreases the reliability of sensory information from plantar mechanoreceptors 37 , 38 and creates unexpected mechanical perturbations when compressive loads are applied and released 39 . There is evidence that the visual system is the primary sensory system used to maintain upright postural control 40 42 , and that standing on a foam surface with eyes open leads to an increase in the reliance on visual and/or vestibular inputs to control posture 43 , 44 , corrective muscle and torque activity 45 , and co-contraction of leg and trunk muscles 46 . Thus, the short-latency postural responses that occur when standing on an instable surface with eyes open is likely to more heavily involve subcortical brainstem and spinal cord structures (e.g., stretch reflex and non-reciprocal inhibition) 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The observation that balance control during the PAD condition was not related to executive function measures is intriguing given that standing on an unstable base of support decreases the reliability of sensory information from plantar mechanoreceptors 37 , 38 and creates unexpected mechanical perturbations when compressive loads are applied and released 39 . There is evidence that the visual system is the primary sensory system used to maintain upright postural control 40 42 , and that standing on a foam surface with eyes open leads to an increase in the reliance on visual and/or vestibular inputs to control posture 43 , 44 , corrective muscle and torque activity 45 , and co-contraction of leg and trunk muscles 46 . Thus, the short-latency postural responses that occur when standing on an instable surface with eyes open is likely to more heavily involve subcortical brainstem and spinal cord structures (e.g., stretch reflex and non-reciprocal inhibition) 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The visual system is the primary sensory system used in maintaining postural control. [66][67][68] Visual stimulation of the peripheral visual field decreases postural sway in the direction of the observed visual stimulus to the anterior-posterior direction rather than the medial-lateral direction. 69 Individuals use peripheral vision for visual stabilization of spontaneous or visually induced body sway to control posture.…”
Section: Postural Control System and Assessmentsmentioning
confidence: 99%
“…They also found that reliance on vision was dominant among the younger population. Although it is a known fact that vision is the primary sensory system used in balance (Merla & Spaulding, 1997; Poole, 1991; Uchiyama & Demura, 2009), it must be noted that one can stand in the dark and remain upright.…”
Section: The Visual Systemmentioning
confidence: 99%